Practicing philosophical dialogue with adolescents: How to foster greater awareness of learning in students - Gagnon, Mathieu; Agundez-Rodriguez, Adolfo; Richard, Amélie; Theis, Laurent; Michaud, Olivier (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
The practice of philosophical dialogue with young people is experiencing significant growth on an international level. Since this practice often takes place within a school context, where one of the main missions is to foster learning, it becomes valuable to conduct studies that document the learning outcomes of students, including their awareness of these outcomes. However, studies in this regard—particularly those comparing students’ awareness across different pedagogical approaches—are nonexistent. This article examines this issue, leading to the conclusion that the way learning sequences are structured may influence students’ perception of the learning they achieve in philosophy.